Ultrahigh brilliance multi-MeV gamma-Ray beams from nonlinear relativistic Thomson scattering - Sarri,G; Corvan,DJ; Schumaker,W; Cole,JM; Di,Piazza A; Ahmed,H; Harvey,C; Keitel,CH; Krushelnick,K; Mangles,SPD; Najmudin,Z; Symes,D; et al. (Physical Review Letters, 2014)
We report on the generation of a narrow divergence (θγ<2.5  mrad), multi-MeV (Emax≈18  MeV) and ultrahigh peak brilliance (>1.8×1020  photons s−1 mm−2  mrad−2 0.1% BW) γ-ray beam from the scattering of an ultrarelativistic laser-wakefield accelerated electron beam in the field of a relativistically intense laser (dimensionless amplitude a0≈2). The spectrum of the generated γ-ray beam is measured, with MeV resolution, seamlessly from 6 to 18 MeV, giving clear evidence of the onset of nonlinear relativistic Thomson scattering. To the best of our knowledge, this photon source has the highest peak brilliance in the multi-MeV regime ever reported in the literature.